MAHAR SECARA BERHUTANG DALAM PERSPEKTIF HUKUM ISLAM - Fajarwati (Jurnal Tahqiqa : Jurnal Ilmiah Pemikiran Hukum Islam, 2022)
Dowry is a dowry that must be given by a husband to his wife. This is contained in the Word of Allah SWT in the Qur'an Surah An-Nba 'verse 4. The purpose of the dowry is to strengthen relationships and foster affection and love. Islam does not limit the amount/level of dowry in a marriage. It is left to humans (women). A good wife is one who does not make the dowry difficult or expensive. Expensing the dowry is something that is hated by Islam, because it will complicate marital relations between fellow humans.